Efektivitas Layanan Aduan Lapor Bupati Berbasis E-Government di Kabupaten Pekalongan - Pratama, Agung Barok; Manasikana, Arina; Fadzlina, Nurul Auliya (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2023)
The public service sector is a reflection of the governance of a government. Poor public service delivery will certainly disrupt the stability of government administration because it will affect the level of public trust in the government. The Pekalongan Regency Government created an e-government-based public complaint service system called the Regent's Report, as an effort to improve public services. This study aims to evaluate the implementation of the Regent's Report complaint system in Pekalongan Regency and to find out the factors that influence the implementation of the Regent's Report complaint system in Pekalongan Regency. This research is a qualitative descriptive study. The results of this study indicate that the Evaluation of the Regent's Report complaint system was carried out by reviewing William Dunn's evaluation theory, among others; effectiveness, efficiency, adequacy, alignment, responsiveness, and accuracy. The Pekalongan Regency Government should increase the leveling and responsiveness points because it was found that the majority of the people did not know about the Regent's Report complaint system. The factors that influence the implementation of the district head's report complaint system consist of supporting factors, namely e-government-based systems and adequate infrastructure, and inhibiting factors, namely budget, human resources and implementation standard guidelines.